2003
DOI: 10.1200/jco.2003.04.190
|View full text |Cite
|
Sign up to set email alerts
|

Kinase Mutations and Imatinib Response in Patients With Metastatic Gastrointestinal Stromal Tumor

Abstract: Activating mutations of KIT or PDGFRA are found in the vast majority of GISTs, and the mutational status of these oncoproteins is predictive of clinical response to imatinib. PDGFRA mutations can explain response and sensitivity to imatinib in some GISTs lacking KIT mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

48
1,574
9
43

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 2,122 publications
(1,674 citation statements)
references
References 36 publications
48
1,574
9
43
Order By: Relevance
“…Furthermore, a recent study demonstrated that in late-stage metastatic GIST, different mutations within the KIT gene resulted in different STI571 effectiveness. 20 In malignant phyllodes tumors, as the lesional cells are also stromal in origin, an understanding or a more comprehensive assessment of the c-kit expression in phyllodes tumors may be crucial for possible future use of STI571 in these tumors. However, as the effectiveness in other soft-tissue tumor of STI571 has not been conclusively demonstrated, it is still too early to speculate on its role in mammary phyllodes tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study demonstrated that in late-stage metastatic GIST, different mutations within the KIT gene resulted in different STI571 effectiveness. 20 In malignant phyllodes tumors, as the lesional cells are also stromal in origin, an understanding or a more comprehensive assessment of the c-kit expression in phyllodes tumors may be crucial for possible future use of STI571 in these tumors. However, as the effectiveness in other soft-tissue tumor of STI571 has not been conclusively demonstrated, it is still too early to speculate on its role in mammary phyllodes tumors.…”
Section: Discussionmentioning
confidence: 99%
“…20 Another tumor that commonly expresses KIT is gastrointestinal stromal tumor (GIST). 21 Successful treatment of metastatic and unresectable GIST with the ATP-competitive protein kinase inhibitor, imatinib mesylate (Gleevec), 22,23 has prompted a search for activating mutations in KIT and related receptor tyrosine kinases in Merkel cell carcinoma. In vitro studies have shown a decrease in proliferation of Merkel cell carcinoma by addition of Gleevec.…”
mentioning
confidence: 99%
“…In both the receptors, the mechanism responsible for kinase activation is mainly represented by gain-of-function mutations, which always affect specific exons (Corless et al, 2004). To date, several types of mutations have been described and the main mutational 'hot spot' is represented by c-Kit exon 11 (Corless et al, 2002;Heinrich et al, 2003).…”
mentioning
confidence: 99%